Analysis of publications on HPV genotype co-infection: a bibliometric study on existing research - Bi, Tianyi; Gong, Yingxin; Mo, Jiayin; Wang, Yan; Qu, Wenjie; Wang, Yaping; Shi, Wenqian; Zhang, Feifei; Sui, Long; Li, Yanyun (Frontiers in Oncology, 2023)
Purpose To identify the bibliometric information of Human papillomavirus (HPV) genotype co-infection in certain literature database over the past two decades. Methods Web of Science was used as the main database to identify all eligible articles focusing on HPV genotype co-infection at the date of October 16, 2022. From this journal database, we identified 463 articles on HPV genotype co-infection, conducted statistical analysis according to the author, journal, publication year and month, country or region, keyword and impact factor. Results The articles included in our analysis were published between 1994 and 2022. The index of citations per year ranged from 170.4 to 13.1. These articles were from 78 countries or regions, with most publications from the United States (n = 73), followed by China (n = 65) and Italy (n = 50). The journal that contributed the most publications on HPV heterotypic gene co-infection was PLOS ONE with a total of 29 articles, followed by JOURNAL OF MEDICAL VIROLOGY (n = 28), INFECTIOUS AGENTS AND CANCER (n = 14) and JOURNAL OF CLINICAL VIROLOGY (n = 12). Among existing research in the field of HPV co-infection, we found that epidemiological distribution and infection mechanism has been the two major topics for scholars, and studies on detection methods for HPV multiple genotypes were also included. Conclusion Over decades, epidemiological studies and mechanism investigationhas been the central topics when it comes to HPV genotypes co-infection. Studies on HPV co-infection remained relatively insufficient, mainly stays in qualitative level while detailed infection data and high quality literature publications were still lack of valuable discussion.